Characterization of agrobiodiversity in the Taquari valley, RS: floristic survey, and agroindustrialization of nonconventional vegetables - Sfoglia, Natalia; Biondo, Elaine; Zanetti, Cândida; Cherobini, Luciane; Kolchinski, Eliane Maria; Sant'Anna, Voltaire (Science & Technology Journals, 2019)
Unconventional vegetables are species whose parts are edible, but incipiently used because they are considered either nonharvested crops or weeds and, mainly, because of the lack of knowledge on their nutritional potentialities. They are elements of the agrobiodiversity that, if valued, may become important for the agroecological production and sustainable rural development. A survey on the species and number of individuals was carried out, as well as the knowledge (among the community members and family farmers) on these species, associated to a discussion based on the literature on the species diversity of nonconventional vegetables, and on its consumption potential and agroindustrialization in the Taquari Valley region. Twenty-one species were identified, out of which 13 showed more than five individuals per square meter; from the total identified species, Parietaria debilis G. Forst, Bidens pilosa L., Oxalis niederleinii R. Knuth, and Rubus rosifolius Sm. stand out for their higher density per square meter. The interviews showed that there is an understanding that vegetable consumption is very important; however, nonconventional vegetables are not recognized as that, and few species, such as Vasconcellea quercifolia A. St.-Hil., Cucumis anguria L., and Hibiscus sabdariffa L. are frequently used and agroindustrialized. There is an ample potential for production and use of nonconventional vegetables in the region and, therefore, a need for further research on these vegetables.
Keywords: food; genetic resources; sustainability